Radiofrequency Ablation of Umbilical Cord for Reduction of Twin Reversed Arterial Perfusion Sequence: A Case Series and a Literature Review - Fatemeh Rahimi Sharbaf; Marjan Ghaemi; Mahboobeh Shirazi; Behrokh Sahebdel; Mansooreh Haghiri; Fatemeh Golshahi (Mashhad University of Medical Sciences, 2022)
Background: Twin reversed arterial perfusion (TRAP) sequence is a rare disorder of monochorionic twins in which the placental anastomoses results in transitioning the blood from the normal fetus to the acardiac twin by a reversed arterial flow. This study aimed to investigate the radiofrequency ablation (RFA) outcome of the umbilical cord occlusion of acardiac twin to reduce TRAP sequence in monochorionic diamniotic pregnancies.Methods: This prospective study investigated 25 cases of monochorionic diamniotic twin pregnancy with one acardiac fetus and selective reduction by RFA in the second trimester of gestational age in a referral hospital affiliated to Tehran University of Medical Sciences, Tehran, Iran, from 2018 to 2019.Results: The mean±SD of gestational age in RFA and delivery were 20.0±3.8 and 35w±6.0 days, respectively, with a survival rate of 84%. A total of nine neonates were admitted to the neonatal intensive care unit, and four miscarriages were recorded in less than 24 weeks. The RFA procedure was successful in all pregnancies for selective termination of the acardiac twin.Conclusion: RFA was a safe and reasonable method in a selective-fetal reduction in acardiac twins for monochorionic pregnancies.